'Greenfields' and 'Brownfields': automotive industrial development in the UK and in Portugal - Pike, Andrew (1996)
The industrial policy in the UK and in Portugal, as in most EU countries, seeks to attract new investment capacity, to create jobs and to promote the impact of the so-called "demonstration efect" of "greenfield" development strategies pursued in the new plants of inward investors on existing or "brownfield" plants. This industrial policy focus is particularly evident in the automobile industry.This paper compares the industrial policy oriented towards the automobile industry in the UK and in Portugal. Two recent "greenfield" investments are analised: Nissan in the North-East region (UK) and Ford/VW in the Setúbal Peninsula (Portugal), as well as three "brownfield" plants: Ford Halewood and GM Vauxhall Ellesmere Port in the North-West region (UK) and Renault in Setúbal (Portugal). The first part starts with a discussion of industrial policy in the automobile sector, the role of "greenfield" development strategies and the "demonstration effect" on "brownfield" plants. Then, the limits of new inward investment are pointed out, basically their problems and restrictions. Afterwards, the structural barriers to the "demonstration effect" within "brownfield" plants are outlined and some possabilities for alternative "brownfield" development strategies are presented.